2002
DOI: 10.1016/s0735-1097(01)01824-1
|View full text |Cite
|
Sign up to set email alerts
|

Repeated sauna treatment improves vascular endothelial and cardiac function in patients with chronic heart failure

Abstract: Repeated sauna treatment improves vascular endothelial function, resulting in an improvement in cardiac function and clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
231
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(247 citation statements)
references
References 32 publications
12
231
1
3
Order By: Relevance
“…12 The dry sauna method sauna has been studied extensively by several groups of Japanese researchers at the University of Kagoshima. 2,[11][12][13][14][15][16][17] Those researchers have utilized this approach in subjecting patients with heart failure to dry sauna at a temperature of 60°C for a period of 15 minutes per session.…”
Section: Sauna Bathing/dry Sauna Methodmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The dry sauna method sauna has been studied extensively by several groups of Japanese researchers at the University of Kagoshima. 2,[11][12][13][14][15][16][17] Those researchers have utilized this approach in subjecting patients with heart failure to dry sauna at a temperature of 60°C for a period of 15 minutes per session.…”
Section: Sauna Bathing/dry Sauna Methodmentioning
confidence: 99%
“…Several studies have shown that systemic vascular resistance (SVR) decreases during and after thermal therapy sessions. 2,11,16,17 The decrease in SVR ranged from 41.5% during thermal therapy 11 to 15.7% 1 day after a 2-week treatment. 2 This decrease in SVR during and after thermal therapy could be considered a potential sign of improved endothelial function in these patients.…”
Section: Clinical Impact Of Thermal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical settings, the major objective of thermotherapy is to achieve an effective treatment outcome with minimal impact on intervening and surrounding tissues [42,43]. It consists of relatively small changes in the core body temperature occasionally for therapeutic purposes [44,45].…”
Section: Thermotherapy For Rehabilitation Of Heartmentioning
confidence: 99%
“…The results suggested that infrared sauna use may be beneficial for lowering blood pressure and waist circumference. Heart studies done by the Mayo Clinic [64] found that infrared sauna therapy significantly improved blood vessel functioning in high-cholesterol, diabetes and smoking patients. The therapy was also found to increase circulation, lower blood pressure, lower blood sugar, and help in weight loss.…”
Section: Infrared Saunasmentioning
confidence: 99%